3D Evaluation Model of Eco-City Planning Based on the Distance Measure. Issue 3 (1st September 2016) - Hong, Ren; Yongjie, Du; Weiguang, Cai; Xianrui, Ma; Peng, Wang; Beibei, Qin; Mingman, Chen
Abstract : With high-speed urbanization and strict requirements on energy conservation and environmental protection, eco-city has become the priority of urban development in China. Governments of all levels promote various eco-city planning schemes within a short term, but most schemes are characterized by randomness and subjectivity. To solve the lack of scientific pre-implementation evaluation for eco-city planning and improve eco-city construction quality, a systematic analysis is conducted in this study from three dimensions, namely, eco-city planning scheme, operating mechanism, and guarantee measures. A 3D evaluation model for eco-city planning is constructed through index selection. Schemes are ranked comprehensively with the distance measure method, and projection analysis is performed with the four-grid evaluation screen. Finally, the 3D evaluation model is applied to evaluate eco-city planning for Shenzhen, Chongqing, and Weifang. Results show that the model can be used to evaluate eco-city planning schemes effectively and comprehensively and offers targeted optimization suggestions in accordance with the evaluation results. Construction of the 3D evaluation model of eco-city planning based on the distance measure to determine the reasonability of eco-city planning reduces the institutional and social costs of eco-city planning practices.